2013
DOI: 10.1259/dmfr.20130082
|View full text |Cite
|
Sign up to set email alerts
|

Small field of view cone beam CT temporomandibular joint imaging dosimetry

Abstract: Acquisitions of individual right and left TMJ volumes using the Kodak 9000 3D CBCT imaging system resulted in a more than ten-fold reduction in the effective dose compared with the larger single field acquisition with the Hitachi CB MercuRay. This decrease is made even more significant when lower tube potential and tube current settings are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Studies that fail to adjust for attenuation differences of the bone and soft tissues may underestimate bone doses by a factor of 2-43. 30,42 Examining the ratio of the bone to bone marrow doses using the means in Table 11 suggests a range of 3.1-4.13 average underestimation of the bone dose if dosemeter values are not corrected for bone attenuation efficiency. This will lead to a 2-5% underestimation of effective dose depending on the size of the FOV.…”
Section: Fov Sizementioning
confidence: 99%
“…Studies that fail to adjust for attenuation differences of the bone and soft tissues may underestimate bone doses by a factor of 2-43. 30,42 Examining the ratio of the bone to bone marrow doses using the means in Table 11 suggests a range of 3.1-4.13 average underestimation of the bone dose if dosemeter values are not corrected for bone attenuation efficiency. This will lead to a 2-5% underestimation of effective dose depending on the size of the FOV.…”
Section: Fov Sizementioning
confidence: 99%
“…Similarly, Luckat et al (15) performed dosimetry of CBCT exams for TMJ region and reported a significant reduction of effective dose when two small FOVs were used in comparison with a large FOV. However, different CBCT devices were used for this purpose: Kodak 9000 for image acquisitions with small FOV and Hitachi CB MercuRay for a single field acquisition including both TMJs.…”
Section: Discussionmentioning
confidence: 99%
“…One factor contributing to this is that most of dosimetry CBCT studies evaluated the dose in exams obtained with large or medium FOVs (4,(10)(11)(12)(13)(14)(15). In such cases, the large FOV is centered on the maxillo-mandibular region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Librizzi et al 13 reported the effective dose from bilateral TMJ examination using a different CBCT device, CB MercuRay (Hitachi Medical, Twinsburgh, OH), resulting in 550 m Sv for either one 9-inch FOV or two 6-inch FOVs. Lukat et al 14 reported an effective dose of 220 mSv from a CB MercuRay using a 9-inch FOV, and 20 mSv from a Kodak 9000 3D (Carestream, Rochester, NY) CBCT using two 5.0 3 3.7 cm FOVs. The difference between the effective doses determined for CBCT and MSCT in the present study, 92 and 124 mSv, respectively, were minor compared with the very large range of effective doses from CBCT examinations of the TMJ in the literature, 20-550 mSv.…”
Section: Discussionmentioning
confidence: 99%